2018
DOI: 10.1186/s13002-018-0232-9
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic differences in the cultural significance of edible and toxic mushrooms among Tsotsil towns in the Highlands of Chiapas, Mexico

Abstract: BackgroundMushrooms are important forest resources, mostly as food, despite the serious health threat posed by toxic species. In the Highlands of Chiapas, numerous wild mushroom intoxications have been registered. While Chiapas has been vastly studied from an ethnomycological perspective, no certainty exists as to how nomenclature systems differentiate edible and toxic species, which species are most culturally significant, and whether sociodemographic factors relate to how well-known they are in the Highlands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
1
16
0
2
Order By: Relevance
“…The majority of regional ethnomycological studies have focused only on fungi species used for consumption. Examples include works from Mexico, such as the study conducted in two municipalities of the Sierra Tarahumara, with 22 recognized edible folk taxa [51]; in Tsotsil town in the Highland of Chiapas with 25 edible taxa [52]; or in Amelaco, Quéretaro, where the authors were able to list 33 taxa [53]. The number of species sold in local markets in Mexico is much higher.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of regional ethnomycological studies have focused only on fungi species used for consumption. Examples include works from Mexico, such as the study conducted in two municipalities of the Sierra Tarahumara, with 22 recognized edible folk taxa [51]; in Tsotsil town in the Highland of Chiapas with 25 edible taxa [52]; or in Amelaco, Quéretaro, where the authors were able to list 33 taxa [53]. The number of species sold in local markets in Mexico is much higher.…”
Section: Resultsmentioning
confidence: 99%
“…Our data showed that non-edible fungi species are key factors in the kosmos, corpus, and praxis of traditional knowledge of wild mushrooms [5]. We identi ed more than 100 non-edible taxa; in contrast, other ethnomycological studies usually mention up to 17 species that are recognized as toxic or poisonous [13,41]. Moreover, the characterization of local knowledge on non-edible mushrooms has been super cial and is generally the result generalizations from edible mushrooms [11,16,19,75].…”
Section: Traditional Knowledge Of Non-edible Mushroomsmentioning
confidence: 89%
“…The names emerge by contrasting non-edible with edible mushrooms, and each ethnotaxon is delimited by certain types of characteristics that allow for its recognition. In this nomenclatural scheme we observed that only the most remarkable species, or the ones that represent health hazards, have a name, but as their relevance declines, so does the interest to assign them names [9,11,13,30,41]. In addition, the names demonstrate the pragmatic character of the nomenclature, where a vast knowledge of morphologic, ecologic, phenologic and qualitative traits is employed to allow the recognition of every ethnotaxon [8].…”
Section: Nomenclature and Discrimination Of Non-edible Mushroomsmentioning
confidence: 98%
See 2 more Smart Citations